Mental Health, Human Capital and Labor Market Outcomes - Christopher Cronin; Matthew Forsstrom; Nicholas Papageorge (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2017)
There are two primary treatment alternatives available to those with mild to moderate depression or anxiety: psychotherapy and medication. The medical literature and our analysis suggests that in many cases psychotherapy, or a combination of therapy and medication, is more curative than medication alone. However, few individuals choose to use psychotherapy. We develop and estimate a dynamic model in which individuals make sequential medical treatment and labor supply decisions while jointly managing mental health and human capital. The results shed light on the relative importance of several drawbacks to psychotherapy that explain patients' reluctance to use it: (1) therapy has high time costs, which vary with an individual's opportunity cost of time and flexibility of the work schedule; (2) therapy is less standardized than medication, which results in uncertainty about its productivity for a given individual; and (3) therapy is expensive. The estimated model is used to simulate the impacts of counterfactual policies that alter the costs associated with psychotherapy.
Keywords: I10; I12; J22; J24; 330; Mental Health; Demand for Medical Care; Labor Supply; Structural Models